2006
DOI: 10.1158/1055-9965.epi-06-0391
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Abnormalities and Risk for Colorectal Cancer in the Physicians' Health Study

Abstract: Background: Obesity and diabetes are established risk factors for colorectal cancer but have mainly been assessed independently. There are few data about whether the metabolic syndrome, which refers to a clustering of cardiovascular disease risk factors thought to be related to insulin resistance, including obesity, type 2 diabetes, hyperlipidemia, and hypertension, is associated with colorectal cancer risk. Methods: During and after the randomized trial of aspirin and B-carotene, 22,071 healthy male physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 60 publications
9
93
1
1
Order By: Relevance
“…Nevertheless, four out of five previous prospective studies (excluding a very small study of 54 cases 26 ), consistently reported a 1.4-1.5-fold significant increased risk of incident or fatal colorectal cancer in subjects with three or more MetS factors present (Table 5). [22][23][24][25] The fifth study showed no such association. 14 In that study, however, hyperglycaemiaFa strong risk factor in our and other studiesFwas not included as a factor of the MetS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nevertheless, four out of five previous prospective studies (excluding a very small study of 54 cases 26 ), consistently reported a 1.4-1.5-fold significant increased risk of incident or fatal colorectal cancer in subjects with three or more MetS factors present (Table 5). [22][23][24][25] The fifth study showed no such association. 14 In that study, however, hyperglycaemiaFa strong risk factor in our and other studiesFwas not included as a factor of the MetS.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, diastolic blood pressure was the only variable that showed an increased risk across quartiles. High blood pressure has in most, 22,23,26,33 but not all, 24,34 previous studies been related to a moderate, but mostly non-significant, increased risk of colorectal cancer incidence or mortality. Based on our observations, we suggest that the WHO cut-off points of risk factors, originally set for prediction of CVD, may also be suitable for estimates of colorectal cancer risk.…”
Section: 4mentioning
confidence: 97%
See 1 more Smart Citation
“…Nine studies were conducted in the USA (16,18,20,32,35,(37)(38)(39)(40) , one in Sweden (42) , five in Korea (6,9,10,22,27) , two in China (23,30) , eight in Japan (8,24,26,28,29,31,36,43) , one in Austria (41) and three in European countries (4,17,34) (Tables 1 and 2). Pooled analysis showed a significant association between serum TAG and CRN (n 29 studies; summary RR = 1·08; 95 % CI 1·05, 1·12, P < 0·00001; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…3 Many studies have shown that general obesity as measured by BMI is positively associated with colon or colorectal cancer in men, [4][5][6][7][8][9][10][11] whereas weaker or no associations have been found in women. 4,6,8,[12][13][14] Findings for rectal cancer risk in association with height, weight or BMI have been inconsistent and nonsignificant.…”
Section: )mentioning
confidence: 99%